PENGARUH BEBAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN KOTA BANDAR LAMPUNG - Malik Malik; M. Zoely Artha Hakim (e-JKPP, 2021)
The problems in this study are: (1) Is there an influence of Workload on the Performance of Employees in the Protocol and Communication Section of the Bandar Lampung City Leaders, (2) Is there any influence of Motivation on the Performance of the Employees in the Protocols and Communication of the Bandar Lampung City Leaders, (3) Is there an influence of Workload and Motivation on Employee Performance in the Protocol and Communication Section of the Bandar Lampung City Management.The research method used in this study is a survey using survey methods. By means of the census it is intended that all populations are also sampled because the population is limited and allows researchers to examine all populations by using questionnaires as a data collection tool. In completing the main data (primary data) also used interviews with section leaders and staff to strengthen and explore factors which cannot (yet) have been revealed in the questionnaire.The results showed that there was a significant influence of Workload and Motivation on Employee Performance in the Protocol and Communication Section of Bandar Lampung City Leaders, the biggest influence of the dimensions of workload forming was the dimension of external factors, while the smallest dimension of the variables forming workload was an internal factor, then The biggest dimension of forming motivation is financial motivation, while the smallest influence of forming variables motivation is non-financial motivation. Based on the results of the study, it can be suggested that the need to increase the division of labor properly, so that the workload can be divided properly, and employee motivation in being increased according to the workload so that employee performance in the Protocol and Communication Section of the leadership of the Bandar Lampung City, can increase as expected.